50 Jahre / Years documenta 1955-2005 : archive in motion (Kassel : Documenta Archiv Kassel Kunsthalle Fridericianum Kassel, 2005)
Abramovic, Marina ; Absalon ; Acconci, Vito ; Acht, René ; Ackermann, Peter ; Adam, Henri-Georges ; Adami, Valerio ; Adams, Mac ; Adams, Robert ; Benin ; Adler, Billy ; Aeschbacher, Hans ; Aeschlimann, Richard ; Afro ; Agam, Yaacov ; Agarwal, Ravi ; Agnetti, Vincenzo ; Ahtila, Eija-Liisa ; Akerman, Chantal ; Albers, Josef ; Albert, Herman ; Alechinsky, Pierre ; Alexander, Peter ; Alfano, Carlo ; Allen, Terry ; Altenbourg, Gerhard ; Althamer, Pawel ; Altmann, Robert ; Ancelovici, Gaston A. ; Andersch, Gisela ; Anderson, Laurie ; Andre, Carl ; de Andrea, John ; Anselmo, Giovanni ; Ant Farm ; Antes, Horst ; Antonakos, Stephen ; Appel, Karel ; Applebroog, Ida ; Arakawa, Shusaku ; Arbeitszeit ; Arbus, Diane ; Archigram ; Archizoom Association ; Ardon, Mordechai ; Armajani, Siah ; Armaly, Fareed ; Arman ; Armitage, Kenneth ; Armleder, John ; Arnoldi, Charles ; Arp, Hans (Jean) ; Arroyo, Eduardo ; Art & Language ; Artaud, Antonin ; Artschwager, Richard ; Asher, Michael ; Ashkin, Michael ; Askevold, David ; Asymptote ; Ataman, Kutlug ; Atget, Eugène ; Attersee, Christian Ludwig ; Auberjonois, René ; Aubertin, Bernard ; Avramidis, Joannis ; Aya & Gal Middle East ; Aycock, Alice ; Azumo, Kengiro ; Bacon, Francis ; Badura, Michael ; Baer, Jo ; Bagnoli, Marco ; Baikas, Nicos ; Bakic, Vojin ; Baldessari, John ; Balka, Miroslaw ; Balla, Giacomo ; Balthus ; Bamgboyé, Oladélé Ajiboyé ; Bandau, Joachim ; Baquié, Richard ; Bargheer, Eduard ; Bargmann, Julie ; Bark, Jared ; Barlach, Ernst ; Barney, Matthew ; Barr, Jerry ; Barrio, Artur ; Barry, Robert ; Bartlett, Jennifer ; Baruchello, Gianfranco ; Baselitz, Georg ; Bass, Saul ; Battke, Heinz ; Batz, Eugen ; Baukhage, Gerd ; Baumann, Andreas ; Baumann, Horst H. ; Baumgarten, Bodo ; Baumgarten, Lothar ; Baumgartl, Monika ; etc.
Duits, Engels
Engels
boek